Thermal Comfort Index Analysis of Padang City Coastal Tour-ism Area Using the Physiological Equivalent Temperature (PET) Method - Sadinda Tsania Suhada; Nofi Yendri Sudiar; Hamdi; Letmi Dwiridal (Universitas Negeri Padang, 2023)
This study aims to determine the category of comfortable thermal sensation in traveling based on the value of the Physiological Equivalent Temperature (PET) thermal index. The research sites were selected in Padang Beach (PP), Air Manis Beach (PAM) and Nirwana Beach (PN). Calculation of perception of comfort using questionnaire data to visitors. PET calculation data is sourced from the Meteorology, Climatology and Geophysics Agency (BMKG) in 2011-2020 and direct measurement data. The results show that the PET thermal sensation category for the Padang City coastal area throughout the year (2011-2020) is included in the